Correlations Between Single-Photon Emission Computed Tomography Parameters of Salivary Glands and Dry Eye Tests in Patients With Sjögren's Syndrome - Huang, Xiaoyu; Xu, Lingjuan; Wang, Wei; Hu, Weikun; Li, Xinyu; Zhang, Hong; Chen, Jing; Li, Guigang (Frontiers in Medicine, 2022)
Objective: To evaluate the correlations between Single-Photon Emission Computed Tomography (SPECT) parameters of salivary glands and dry eye parameters in patients with Sjögren’s syndrome (SS).Methods: A total of 28 patients with SS participated in this study. Dry eye assessments include tear film break-up time (TBUT), corneal fluorescein staining scoring (CFS), Schirmer’s I test (SIT) examination and SPECT of salivary gland. The following quantitative parameters were derived from SPECT imaging for salivary glands: uptake index (UI), the time needed to achieve the minimum counts after Vit C stimulation (Ts), and excretion fraction (EF). The relation between the aforementioned parameters and TBUT, CFS and SIT were analyzed with SPSS 22.0 software. Results: all the 28 eyes of the 28 subjects were examined. The mean SIT was 6.04±4.64 mm/5 min (0-18 mm/5 min); the mean CFS was 3.07±2.65 (0 - 10) and the mean BUT was 2.11±1.97 sec (0 - 9 sec) . The mean EF value was 0.52±0.12 (0.26 - 0.75) in parotid glands and 0.45±0.10 (0.30 - 0.67) in submandibular glands, respectively. The mean UI value was 9.33±1.68 (6.03 - 13.20) in parotid glands and 9.92±1.48 (7.08 - 12.60) in submandibular glands respectively. The mean Ts (min) was 5.32±3.01 (2.00 - 12.00) in parotid glands and 11.09±7.40 (2.00- 29.00 min) in submandibular glands respectively. It was found that EF positively correlates with SIT in patients with SS (r=0.499 and 0.426 in parotid glands and submandibular glands, with P < 0.05), while no significant correlation was found between the UI,Ts and CFS ,TBUT (P > 0.05).Conclusions: EF (but not UI or Ts) could reflex the dysfunction of salivary glands in SS patients. So, EF may be a valuable parameter for the diagnosis of SS patients with lacrimal gland secretion dysfunction.